Sistem Pakar Diagnosa Gangguan Pencernaan Menggunakan Metode Forward Chaining Berbasis Android - Natanael Iwan Santosa (Universitas Asahan, 2022)
An expert system is a system that adopts human intelligence to solve problems as an expert does. The digestive system has a function to refine food, and has a function to get rid of food waste that is no longer needed by the body, if food waste is not removed it will cause toxins to the body. Digestive disease is a disease that interferes with the work of the digestive system caused by unhealthy food, unbalanced nutrition, poor diet, infections and disorders of the digestive organs. Android is a smartphone software created by Google. Android is open source which allows many parties to develop applications. The purpose of this study is to help shorten the time doctors diagnose patients and can make it easier for patients to diagnose the symptoms they are experiencing. The method that the author uses is forward chaining, which is an approach based on existing data. Tracking starts with input information, then draws conclusions.